Method for improving the quality of service of request signals in information systems - Svyd, I.V.; Sukhorukov, D.O.; Korotich, O.V.; Machonis, T.S. (Radiotekhnika, 2023)
The work notes that the request information systems are an important component of information support for air traffic control and airspace control systems. Interrogative information systems include: secondary radar systems, national identification radar systems and short-range navigation radio systems. It is shown that the characteristics of the process of servicing request signals in an aircraft transponder have a significant impact on the statistical properties of the response signal flow, which ultimately, as a consequence, affects the efficiency of the entire radar channel for transmitting response signals with an active response. It is pointed out that one of the important characteristics of the process of servicing request signals in an aircraft transponder is its correlation function, based on the analysis of which one can conclude the choice of the type of response signal flow and the structure of the aircraft transponder. This makes it possible to achieve: increasing the probability of service, increasing the probability of detecting an air object, reducing the root-mean-square error in estimating the azimuth of an air object and increasing the reliability of the transmission of flight information from the observed board of an air object. The article analyzes the possibility of improving the quality of request service by managing the flow of request signals in a network of request information systems. It has been shown that the correct choice of repetition periods of request signals in the area of joint operation of request information systems makes it possible to reduce the likelihood of interaction between individual request signals. Also, as a consequence, it makes it possible to increase the noise immunity of the interrogative information systems under consideration that are part of the specified information system.